Do the Young Have Equal Voting Power as the Elderly: Population Composition of Electoral Districts and Vote Value Parity - 최슬기 (Journal of Asian Sociology, 2023)
This study sets out to identify the degree to which a vote’s value is unequally weighted due to heterogeneous population compositions across electoral districts. The National Assembly Elections and metropolitan and provincial council elections conducted from 2012 to 2022 in South Korea are analyzed. Analysis results provide that the unequal vote value parity has been addressed to a certain extent. At the election in 2016, when the new demarcation of the electoral districts was implemented, gaps in vote values among different age groups have dropped sizably. However, the 2020 election showed a slightly rebounding trend, presumably reflecting the growing size of the elderly population. At the provincial council elections I found that there were still notable gaps in vote values. It means that heterogeneity of population sizes and age structures across electoral districts make the young have less voting power comparing to the elderly. Therefore, this study proposes to give a heed and to be prepared to ensure the vote parity at the backdrop of the aging population.